2018
DOI: 10.1371/journal.pone.0194364
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to air pollution and self-reported effects on Chinese students: A case study of 13 megacities

Abstract: Air pollution causes severe physical and psychological health complications. Considering China’s continuously-deteriorating air quality, this study aimed to assess the self-reported effects of air pollution on the behavior and physical health of the students of 13 densely populated cities, and their awareness, practices, and perception of air pollution and its associated public health risks. A detailed, closed-ended questionnaire was administered to 2100 students from 54 universities and schools across China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 95 publications
1
30
0
Order By: Relevance
“…A large number of studies have shown that air pollution, especially smog pollution, can greatly affect people's behavior and psychology, such as reducing people's outdoor activities, increasing people's discomfort, causing irritability, depression, etc. [11,12]. These behavioral and psychological changes will significantly affect people's consumption behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies have shown that air pollution, especially smog pollution, can greatly affect people's behavior and psychology, such as reducing people's outdoor activities, increasing people's discomfort, causing irritability, depression, etc. [11,12]. These behavioral and psychological changes will significantly affect people's consumption behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that smog pollution not only affects people's health, increases the risk of cardiovascular and cerebrovascular diseases, cancer, etc. [9,10], but also significantly affects people's behavior [11,12]. When air pollution is severe, people are more willing to stay indoors and reduce the time of outdoor activities [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, [26] revealed the vulnerable population clusters based on innate factors, integrated environmental, social or behavioral factors and unusually high exposures. Likewise, [27] depicted that long-term exposure to air pollution on Chinese students had a robust effect on their behavior and psychology along with their physical health. However, the behavioral health effects were recorded on a Likert scale for various behaviors, i.e., difficulty in concentration, feeling dry, dizziness, nausea, noticeable odors, highstress levels, fatigue/drowsiness, too hot temperature, and too cold temperature, which were grouped and denoted as "B".…”
Section: Independent Variablesmentioning
confidence: 99%
“…PM concentrations are particularly elevated in some developing countries, where they were shown to be well above the upper limit recommended by the World Health Organization's guidelines [5], thus being regarded as a hazard to the health and the quality of life of people living in such areas [1,6].…”
mentioning
confidence: 99%